Comparative Investigation of Amino Acids Content in the Dry Extracts of Juno bucharica, Gladiolus Hybrid Zefir, Iris Hungarica, Iris Variegata and Crocus Sativus Raw Materials of Ukrainian Flora - Olha Mykhailenko; Liudas Ivanauskas; Ivan Bezruk; Roman Lesyk; Victoriya Georgiyants (MDPI AG, 2020)
The aim of this research was the comparative study of the amino acids content in the dry extracts of Iridaceae plants of Ukrainian flora: Juno bucharica leaves and corms, Gladiolus hybrid Zefir leaves, Iris hungarica and Iris variegata rhizomes, and Crocus sativus stigmas, flowers, leaves and corms. A gas chromatography−mass spectrometry (GC−MS) method has been used. Separation of amino acids in the samples was carried out using a Shimadzu GC-MS-QP2010 equipped with an Rxi-5ms (Restek Corporation capillary column (30 m long, 0.25 mm outer diameter and 0.25 µm) with a liquid stationary phase (5% diphenyl and 95% polysiloxane) after derivatization with N-(t-butyldimethylsilyl)-N109 methyltrifluoroacetamide (MTBSTFA) reagent. The results obtained have shown that extracts from the aerial parts of plants investigated have a higher amino acid content and more diverse composition than the underground organs. Experimental data showed that Crocus leaves and Juno leaves extracts contain the highest general content of amino acids—31.99 mg/g and 14.65 mg/g respectively. All samples showed a high content of L-pyroglutamic acid (0.33−12.35 mg/g). Moreover, Crocus leaves and Juno leaves extracts had the most suitable amino acids composition and are prospective for further pharmacological studies.